Action research plan: a methodology to examine the impact of artificial intelligence (AI) on the cognitive abilities of university students - Qian Xu (Springer, 2024)
Abstract This research suggests a methodology to examine the effectiveness Artificial Intelligence (AI) on the cognitive abilities of college students so that future researchers can utilize this experimental project to focus on how AI-powered Intelligent Tutoring Systems (ITSs) affect learning outcomes. As AI continues to revolutionize all walks of life, so has its integration with education. ITS is a key application of AI in education, providing a personalized learning experience by analyzing student data and tailoring instructional materials accordingly. This provides a research program to study the effectiveness of ITS in improving cognitive skills such as memory, critical thinking, and problem solving abilities in college students. The research project combined quantitative and qualitative research methods including surveys, pre-tests, post-tests, and in-depth interviews to assess the cognitive differences between students using ITS and those using traditional learning methods. The research project also recognized potential challenges, such as dependence on technology and the risk of increased educational inequality. The action research program concluded by advocating for a balanced integration of AI into education, highlighting the need for ongoing research to optimize its use across different stages of education and to ensure equitable access to AI-powered tools.